RESEARCH OF THE MANAGEMENT OF INTERNATIONAL CORPORATE BUSINESS UNITS BASED ON THE USE OF INTERNATIONAL FACTORS OF ECONOMIC GROWTH (BASED ON THE EXAMPLE OF CONSULTING SERVICES) - PLYASKINA, Alona; YAKYMCHUK, Tetyana; ZIUBANOV, Hlib (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Scientists divide the entire set of consulting companies in the world into several groups. Thus, the first group includes the "big four" companies. The second group of consulting companies are the so-called "thought factories", which do not just provide consulting services, but offer an unusual and non-standard way out of a difficult situation, offering creative ideas.The next group of companies are subject-oriented companies whose activities are limited to one or more areas, for example, marketing research, recruitment or business planning. Most research results show that the sector of consulting services is developing at a faster pace than other sectors of the world economy. In the developed countries of the world, the share of the service sector is constantly growing, while the positive trend of this sector is characterized by the dynamic development of the consulting services market. Summing up, it is possible to state with great certainty (as evidenced by research results) that the sector of consulting services is developing at a faster pace than other sectors of the world economy. In the developed countries of the world, the share of the service sector is constantly growing, while the positive trend of this sector characterizes the development of the consulting services market. Let’s focus on the consulting process, which is related to agricultural products, because it is more complicated than industrial and other types of consulting, which is determined by the variety of methods, techniques and its implementation. The difference between agricultural business and other types of business.